2018
DOI: 10.3390/medsci6010013
|View full text |Cite
|
Sign up to set email alerts
|

23rd International Symposium on Infections in the Critically Ill Patient

Abstract: IntroductionThis 23rd International Symposium on Infections in the Critically Ill Patient aims to review current concepts, technology and present advances in infections in critically ill patient.Sepsis, Pulmonary Infections and their therapeutic and preventive strategies will be the topics presented by international experts who will review and update sepsis as a global international problem. New guidelines of Surviving Sepsis campaign, fluid therapy and vassopressors, a balance view between personalization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Central venous oxygen saturation (ScvO 2 ) can be used for targeted screening of patients with early sepsis (5). In addition, a study has found that regional cerebral oxygen saturation (rScO 2 ) is closely related to ScvO 2 (6). The present study included 80 children with sepsis-related encephalopathy who were admitted to the Pediatric Intensive Care Unit (PICU) of the Children's Hospital Affiliated to Zhengzhou University (Zhengzhou, China) from January 2015 to January 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Central venous oxygen saturation (ScvO 2 ) can be used for targeted screening of patients with early sepsis (5). In addition, a study has found that regional cerebral oxygen saturation (rScO 2 ) is closely related to ScvO 2 (6). The present study included 80 children with sepsis-related encephalopathy who were admitted to the Pediatric Intensive Care Unit (PICU) of the Children's Hospital Affiliated to Zhengzhou University (Zhengzhou, China) from January 2015 to January 2018.…”
Section: Introductionmentioning
confidence: 99%
“…6 It is accounted for that TC sedate is the beside the biggest utilized as a part of the world, representing right around 33% of the anti-infection agents creation and utilization. 7 , 8 With the unnecessary gathering of antibiotic agents in the human body, 9 they can incite nephropathy, influence kidneys, and different changes, for example, mutagenic and teratogenic impacts. 5 The presence of TC drug in water conditions will influence the structure and action of microorganisms, which subsequently changes the natural structure of the microbial vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…Tetracycline (TC) drug is broadly utilized as a part of different perspectives, for example, bacterial infection, horticulture, and domesticated animal products . It is accounted for that TC sedate is the beside the biggest utilized as a part of the world, representing right around 33% of the anti-infection agents creation and utilization. , With the unnecessary gathering of antibiotic agents in the human body, they can incite nephropathy, influence kidneys, and different changes, for example, mutagenic and teratogenic impacts . The presence of TC drug in water conditions will influence the structure and action of microorganisms, which subsequently changes the natural structure of the microbial vegetation. , In order to eliminate the residual antibiotics in ecological water, the current innovation is primarily reliant on activated carbon adsorption, coagulation–flotation, ultrasound degradation, and membrane bioreactor .…”
Section: Introductionmentioning
confidence: 99%